KAJI EKSPRIMENTAL PEMBANDINGAN KETELITIAN MESIN CNC MILLING DENGAN KONTROL SMC DAN MESIN CNC MILLING DENGAN KONTROL ESP32 WIFI - Hermana, Rifki; Setyoadi, Yuris; Fahrur Aza , Muhammad (Politeknik Bumi Akpelni, 2022)
Computerized Numerical Control (CNC) is one of the developments of automatically operated machining technology that can support the need for the demand for a product that has a complex shape, high accuracy and can work on objects that cannot be done with conventional machinery. CNC Milling in the industry still has an expensive price, both the price of the hardware and software used to operate the CNC Milling machine. Therefore, CNC milling machines are only used in large industries while the middle and lower industries still use CNC milling machines. This makes medium-sized industries less competitive with large industries in production results, both in terms of speed efficiency and accuracy. then research was carried out in the form of CNC design and design that uses an ESP32 wifi-based Offline Controller as an application that supports the CNC machine work process. This research is an experiential review of comparing the accuracy of CNC milling machines with SMC controllers and CNC milling machines with ESP 32 wifi controllers. From the results of the tests carried out as many as 10 times the milling machining process using CNC with SMC control obtained three values that exceeded the tolerance limit, namely one each on the dimensions of length, width and height or depth. While the results of the milling process using a CNC milling machine with ESP32 wifi control obtained six values that exceeded the tolerance limit, namely two each on the dimensions of length, width and height or depth. So it can be concluded that CNC with SMC control is more accurate because the percentage of failures is less compared to CNC with ESP32 wifi control